1994
DOI: 10.2118/25254-pa
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phase Behavior on Bypassing in Enriched Gasfloods

Abstract: Summary Enriched gasfloods incorporate a complex interaction of heterogeneity, fingering, multiphase flow, and phase behavior. Experiments and simulations indicate that the optimum solvent enrichment in high-viscosity-ratio secondary gasfloods can be below minimum miscibility enrichment (MME). The compositional path and resulting mobility profile in multidimensional multiple-contact miscible (MCM) or immiscible floods are different from their 1D counterparts for high-viscosity-ratio floods in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 12 publications
2
27
0
Order By: Relevance
“…The results presented here illustrate a pore-scale mechanism, which could partly explain the previous reports (Shyeh-Yung 1991;Burger et al 1994;Thomas et al 1994;Soroush and Saidi 1999) that near-miscible gas injection could be a very effective oil recovery mechanism. The pore-scale experimental results presented here suggest that (to benefit from this mechanism) gas floods should be either near-miscible or multiple contact miscible (MCM) where two-phase flow is still possible behind the gas front.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results presented here illustrate a pore-scale mechanism, which could partly explain the previous reports (Shyeh-Yung 1991;Burger et al 1994;Thomas et al 1994;Soroush and Saidi 1999) that near-miscible gas injection could be a very effective oil recovery mechanism. The pore-scale experimental results presented here suggest that (to benefit from this mechanism) gas floods should be either near-miscible or multiple contact miscible (MCM) where two-phase flow is still possible behind the gas front.…”
Section: Discussionsupporting
confidence: 84%
“…2D simulation studies (Burger et al 1994; Thomas et al 1994) have demonstrated that injectant with less enrichment than that required for first-contact miscible with the oil often yields optimum oil recoveries owing to better sweep efficiencies in heterogeneous reservoir models. Field-scale simulations show that near-miscible solvents are attractive because of improved sweep over miscible solvents (Pande 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2D simulation studies (Burger et al 1994; Thomas et al 1994) have demonstrated that injectant with less enrichment than that required for first-contact miscible (FCM) with the oil often yields optimum oil recoveries owing to better sweep efficiencies in heterogeneous reservoir models. Field-scale simulations show that near-miscible solvents are attractive because of improved sweep over miscible solvents (Pande 1992).…”
mentioning
confidence: 99%
“…Field-scale simulations show that near-miscible solvents are attractive because of improved sweep over miscible solvents (Pande 1992). Burger et al (1994) showed that economically optimum enrichment in high-viscosity-ratio secondary gasfloods could be operated at pressures below the MMP. Thomas et al (1994) reported that gas-oil IFT can be reduced adequately under near-miscible conditions and that zero IFT is unnecessary for effective displacement processes in realistic porous media.…”
mentioning
confidence: 99%